Are we ready to describe response or progression to immunotherapy in lung cancer?. (June 2019) - Guaitoli, Giorgia; Baldessari, Cinzia; Bertolini, Federica; Tomasello, Chiara; Cascinu, Stefano; Barbieri, Fausto
Graphical abstract: Abstract: Immune checkpoint inhibitors have changed history and management of different tumor types, including non-small cell lung cancer (NSCLC). Response patterns may be more heterogeneous than those seen with cytotoxic chemotherapy. Besides atypical response patterns, new types of outcome should be taken into account such as pseudo-progression (PP) and hyper-progressive disease (HPD). PP is described as initial tumor increase or appearance of new lesions followed by their shrinkage during immunotherapy treatment while HPD is a rapid and severe pattern of progression with a not yet univocal definition. Physiopathology and underlying mechanism of these phenomena are not completely understood and in absence of reliable clinical and biological markers of response to immunotherapy, radiological evaluation remains a key point in clinicians' decision-making process but further efforts would be useful to identify a unique system of evaluation.In this review we summarize the main radiological criteria available in the evaluation of response to checkpoint inhibitors and we describe peculiar response patterns such PP and HPD with a focus on lung cancer.